The effect of food supplementation on nutritional status of severemalnourishment children aged 12-59 months in Sleman District, Yogyakarta Special Region - Soeroyo Machfudz, Ahmad Lubaid Endy Paryanto Prawirohartono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Malnutrition and malnourishment are still big problems among children in Indonesia. Age between12 to 59 months is the most important and critical time periods for the physical and intelligencedevelopment of children. Therefore, the children should obtain a good health care and nutritionaccording to their needs. The purpose of this study was to evaluate the influence of foodsupplementation on the nutritional status of children in Sleman District, Yogyakarta SpecialRegion. This was a quasi experimental study involving 60 severe malnourishment children betweenthe age of 12-59 months from Sayegan Sub Districts. Body weight and height of the childrenwere measured before and after food supplementation. Food supplements were given for 100days. The outcome of this study was the change of nutritional status based on Z-score accordingto the Ministry of Health classification adopted from WHO-NCHS (World Health Organization-US National Center for Health Statistics) recommendations. According to Z score for weight-forage(WAZ), the food supplementation did not improve the nutritional status of children. Althoughthe nutritional status of 25.87% children increased and the mean of WAZ significantly increased1.04 to be -3.29 after supplementation (p<0.05), the mean of nutritional status of the childrenwas still the worst (WAZ <-3SD). According to Z score height-for-age (HAZ), foodsupplementation did not improve nutritional status of the children either. The mean of HAZbefore food supplementation (-2.53) was not signifantly different compared to after foodsupplementation (-2.45). Moreover, mean of nutritional status of the children after foodsupplementation was still short (HAZ <-2SD). According to Z score weight-for-height (WHZ),food supplementation improved the nutritional status in 86.21% children. The mean of WHZsignificantly increased 1.13 from -3.35 to be -2.22 after food supplementation (p<0.05) indicatingthe change of nutritional status from wasted (WHZ <-3SD) to thin (WHZ <-2SD to ï³ï -3SD). Inconclusion, food supplementation on children aged 12-59 months succeeds to improve theirnutritional status according to WHZ.Keywords: poor family - nutritional status - children - severe malnourishment - Z-score